Heart disease prediction using machine learning algorithms - Ali, Musfiq; Khan, MD. Iftiyar; Imran, Masud Al; Siddiki, Musnath (BRAC University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.